Upaya Peningkatan Kualitas Bawang Merah Melalui Penggunaan Mesin Pengering di Desa Karanganyar, Cilacap - Sari Widya Utami; Galih Mustiko Aji; Artdhita Fajar Pratiwi (Politeknik Negeri Cilacap, 2026)
Unpredictable weather conditions during the traditional drying process pose a challenge to shallot farmers in the Rejeki Lancar farmer group in Karanganyar Adipala village in reducing yield losses. Adequate water content is essential for maintaining the quality of shallots ready for sale and storage. Therefore, a drying technology capable of maintaining and improving shallot quality is needed through the use of an electric drying machine. The community service project was implemented using the community-based research (CBR) method with a participatory approach by the farmer groups. The activity stages included observation and discussion, tool design and construction, tool testing and calibration, training and mentoring, and evaluation. The implemented drying machine can dry shallots in 21 hours, whis typically takes 7-9 days. This community service activity increased farmers knowledge and skills in shallot drying technology by 15,71 %. In addition to shortening the drying process, the electric-powered drying machine produces a more uniform moisture content, resulting in improved and more consistent shallot quality. The implementation of this technology is expected to reduce postharvest losses and enhance the competitiveness and sustainable income of shallot farmers.